Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. Obstacles to Applying the Re-Engineering in Public Secondary Schools in the Suburbs of Jerusalem. Aatka Abd Rabo Alkhatib, Prof. Dr. Ashraf Mohammed Abu Khairan 2. Degree of Contribution of Training Patterns at the Specialized Institute for Professional Training of Teachers in the Professional Development of Public School Teachers in the Sultanate of Oman Researcher/ Badria bint Saleh bin Salem Al-Ghailani, Dr. Rabie bin Amurr bin Ali Al-Dhuhli 3. Effectiveness of the Bridges Learning Program in Enhancing Educational Elements from the Perspective of Teachers in the Northern Mazar Governorate Dr. Fatima Saleh Ali Al-Khateeb 4. The reality of endowment management in emerging Saudi universities to finance university education from the point of view of academic leaders and employees Saeed Omair Mohammed 5. The Islamic foundation of the theory of human relations and its educational applications Dr. Ali Hassan Al-Asiri 6. Psychometric Properties for the Jordanian version of the Young Mania Rating Scale (YMRS) Mr / Moamen Ali Awakleh, Mr / Mohammed Ahmed Al-Emad